Penyampaian Alur Informasi Rawat Jalan Kepada Petugas Unit Rekam Medis Puskesmas Gempol - Maulana, Agung Firman; Rakhmawati, Fitria; Sari, Ika Puspita; Yusmanisari, Eka (Jurnal Abdimas Jatibara, 2023)
This community service activity has the aim of providing direction to patients who register as patients so they do the registration requirements of outpatients at the Gempol consultation room. There are still outpatients who don't recognize the wants to register. this could produce obstacles for alternative outpatients. to beat these problems, socialization and education were disbursed for officers and patients by creating brochures. The results achieved in community service activities at Gempol Health Center are the delivery of outpatient data flow to officers within the case history unit running smoothly. All officers understand all the requirements for patient data flow so officers will offer information to patients who are in accordance with the flow requirements. solely a number of outpatients don't recognize the wants on the grounds that they are doing not know and typically patients only bring a few requirements. when distributing brochures, and being given direct information regarding the outpatient information flow by the community service team, patients are expected to fulfill the requirements once they come back to outpatient registration.